PERANCANGAN SISTEM PENDUKUNG KEPUTUSAN PENEMPATAN PESERTA KERJA PRAKTIK PADA DIVISI KEMENTERIAN AGAMA - Rossi Oktavianti (CV. Denasya Smart Publisher, 2026)
The increasing number of internship participants at the Regional Office of the Ministry of Religious Affairs of South Sumatra (Kanwil Kemenag Sumsel) requires a more structured decision-making system to ensure appropriate placement. The current manual placement process often causes division overload, uneven distribution, and mismatches between interns’ skills and division needs. This research proposes the design of a web-based decision support system (DSS) for internship placement using the Rapid Application Development (RAD) method and the Decision Tree algorithm (C4.5) as the main classification model. The data considered include intern profiles, division capacity, academic background, skill set, and interests. Using the Decision Tree algorithm, placement recommendations are generated by mapping the relationships between intern attributes and suitable divisions in a hierarchical decision model. RAD supports rapid system development through iterative prototyping and continuous user feedback. The result of this study includes system workflow, BPMN diagram, use case diagram, activity diagram, class diagram, and user interface mockups. Based on the literature and simulated data, the Decision Tree-based system provides interpretable, rule-based recommendations that can support more objective and balanced placement decisions. This conceptual design is expected to optimize intern distribution across divisions and improve the efficiency of managing the internship program at Kanwil Kemenag Sumsel.